Effect of Prenatal Yoga on Blood Pressure Among Pregnant Women: A Pre-Experimental Study at Grogol Primary Health Center - Farokah, Atik; Fadia, Rahmanda Aqiella (Jurnal Kebidanan Midwiferia, 2026)
Pregnancy is a critical period that presents various physical and psychological challenges for women. One common issue encountered during pregnancy, particularly in the first and third trimesters, is sleep disturbance. Hormonal changes during pregnancy are one of the primary factors contributing to poor sleep quality. Inadequate sleep in pregnant women may also lead to elevated blood pressure (preeclampsia) in subsequent trimesters. One non- pharmacological intervention to address these issues is physical activity, such as prenatal yoga. Methods: This research is a quantitative study with a pre-experimental research design using the One Group Pretest-Postest method. The sample size for this study was 37 pregnant women in their second and third trimesters. Purposive sampling was used. The instruments used were an observation sheet to measure blood pressure. Data analysis was conducted using the Wilcoxon Signed-Rank Test. Results: Prior to the prenatal yoga intervention, the majority of participants experienced elevated blood pressure-19 respondents (51,4%) with high diastolic pressure. Following the prenatal yoga sessions, significant improvements were observed in both blood pressure, with a p-value of 0.000 (<0.05). Conclution : Prenatal yoga has a significant effect on reducing blood pressure in pregnant women at the Grogol Public Health Center